THE PRINCIPLE OF EQUAL TAX, GENERALITY, PROPORTIONALITY AND SOCIETY IN PERU - Mendoza Pérez, Raúl (2014)
Comparing if tax principles of equality, generality, and apply proportionality observed in the data provided by the authorities of the Peruvian State. In the present work, that were used from the data found in the Public Budget Act for fiscal year 2014, National Customs and Tax Administration (SUNAT) applying the deductive method. Also, differences between tax principles and data provided by the State and is suggested to invest in the poorest cities in Peru, considering the signifi-cant revenue (taxes) and representing 70% of public expenditure was found.